Incidence of Karnal bunt and Ear cockle in Punjab during 2005-2012 - INDU SHARMA*; R.C. SHARMA, RITU BALA, DAMAN JEET KAUR (Indian Phytopathology, 2013)
Punjab is called as â€œWheat Bowlâ€ of India contributing about 60 per cent wheat in national grain pool. The surplus of wheat can be traded in international market provided there is no non tariff barrier like Karnal bunt. Intensive cultivation and monoculture of wheat in Punjab has lead to the occurrence of seed borne diseases like loose smut, flag smut, Karnal bunt (KB), black point and ear cockle nematode. Among these, Loose smut (Ustilago segetum var. tritici), Karnal bunt (Tilletia indica) and Ear cockle nematode (Anguina tritici) diseases were designated as high risk diseases and minimum tolerance levels were fixed for them in foundation and certified seed. Information on status of KB from 1998-2004 and ECN from 1994-2001 in Punjab has been already been reported (6, 8). The present investigation is an effort to highlight the status of KB and ECN in different districts/grain markets of Punjab during the last seven years. KB free wheat may be procured for export either by segregation at grain market level or by contract farming.